Allah wants you to be rich: foundations of Muslim career development in al-Ghazālī's Iḥyā’ ‘Ulūm al-Dīn - Ssekamanya, Siraje Abdallah; Badzis, Mastura; Ismail, Khamsiah (IIUM Press, 2017)
While Muslims comprise about a quarter of the world population, they control far less than 25% of global wealth. With few exceptions, Muslim countries are among the poorest in the world. To make things worse, Muslim preachers tend to justify this status quo by teaching that Allah prefers Muslims to be poor. Al-Ghazali’s views are often invoked in justifying this assertion. This paper argues that Allah wants to see His servants wealthy and that al-Ghazali’s emphasis on poverty was an educational strategy. Otherwise, a careful reading of his magnum opus, Ihya’ ‘Ulum al-Din shows that not possessing material wealth is not the ideal situation of a Muslim. The ideal is to have one’s soul focused on being mindful of Allah and detached from material possessions, thereby giving them away without hesitation whenever need arises. We end by highlighting the implications of this understanding of al-Ghazali’s work on the career development of Muslims in school and beyond.